2018
DOI: 10.1371/journal.pone.0205221
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive awareness in attention deficit hyperactivity disorder

Abstract: ADHD is considered a disorder of self-regulation. Recent research has shown that awareness of bodily states, referred to as interoceptive awareness, crucially contributes to self-regulatory processes. Impaired self-regulation in ADHD has been explained in terms of arousal regulation deficits in ADHD (the state regulation deficit (SRD) account). There is now ample support for the SRD account, however the exact reason for arousal regulation difficulties is not yet known. The SRD account explicitly refers to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…This pattern was confirmed in a meta-analysis of fMRI studies of timing in ADHD (Hart et al, 2012). Finally, a recent study by Wiersema and Godefroid (2018) did not reveal a significant difference between patients and healthy controls in the execution of interoceptive tasks, suggesting preserved interoceptive awareness in this clinical population. Overall, the research examined previously does not provide support to the hypothesis of a linking between interoception and timing deficits in ADHD.…”
Section: Attention-deficit Hyperactivity Disordersupporting
confidence: 57%
“…This pattern was confirmed in a meta-analysis of fMRI studies of timing in ADHD (Hart et al, 2012). Finally, a recent study by Wiersema and Godefroid (2018) did not reveal a significant difference between patients and healthy controls in the execution of interoceptive tasks, suggesting preserved interoceptive awareness in this clinical population. Overall, the research examined previously does not provide support to the hypothesis of a linking between interoception and timing deficits in ADHD.…”
Section: Attention-deficit Hyperactivity Disordersupporting
confidence: 57%
“…Interoception is crucial for self‐ and emotion‐related regulation (Craig, 2009), and as children with ADHD have been found to have emotion regulation problems (Shaw et al, 2014), research on the divergent interoceptive performance in children with ADHD is warranted. To‐date, only two studies measured IA comparing adults with pre‐existing ADHD diagnosis and controls (Kutscheidt et al, 2019; Wiersema & Godefroid, 2018), both adopted the classic heartbeat tracking task. The former study suggested preserved IA in ADHD adults, but the latter showed contrary results indicating that ADHD adults were also experiencing difficulties in detecting their own internal bodily signals.…”
Section: Introductionmentioning
confidence: 99%
“…The BPQ-BA by Porges [27] is a very common reference as a questionnaire of interoception in the recent literature (e.g. [4,[35][36][37][38][39][40][41]) although clearly exteroceptive signals are also included (e.g. "During most situations I am aware of noises associated with my digestion").…”
Section: Introductionmentioning
confidence: 99%